Faktor – Faktor yang berhubungan dengan Kejadian Hipertensi di Poli Klinik Penyakit Dalam RSUD Kota Kendari Tahun 2016 - Sahmad, Sahmad (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Hypertension is a chronic medical condition in which increase in blood pressure above the agreed blood pressure. Overview of The results of the measurement of systolic and diastolic blood pressure ranged from 140/90 mmHg. Hypertension that is not well controlled will lead to health problems more serious conditions such as heart attack, heart failure and stroke. Destination This study was to determine the relationship between obesity, diet, and smoking habits with the incidence of hypertension. This research is analytical descriptive research using a Cross Sectional approach Study. The population in this study were hypertensive patients who visited the The Internal Medicine Clinic of the Kendari City Hospital, which was later chosen to be the sample by Accidental Sampling and meet the criteria for the sample determined as many as 33 respondents. Collecting data by means of observation and questionnaires. The results of the study were processed using the Kolmogorov-Smirnov Test with a significance level of < 0.05. The results of the bivariate analysis showed that there was a relationship between obesity (p = 0.028), diet (p = 0.009), and smoking habits (p = 0.018) with the incidence of hypertension in the Internal Medicine Clinic at the Kendari City Hospital. Suggestion, Society needs to carry out orderly healthy behavior by not smoking, reducing excessive eating patterns, and exercising regularly to avoid hypertension. The attention of health workers is increased to provide more adequate knowledge about hypertension to the public